Proteomic and Antibody Profiles Reveal Antigenic Composition and Signatures of Bacterial Ghost Vaccine of Brucella abortus A19 - He, Chuan-Yu; Yang, Jiang-Hua; Ye, Yin-Bo; Zhao, Hai-Long; Liu, Meng-Zhi; Yang, Qi-Lin; Liu, Bao-Shan; He, Sun; Chen, Ze-Liang (Frontiers in Immunology, 2022)
Brucellosis is an important zoonotic disease that causes great economic losses. Vaccine immunisation is the main strategy for the prevention and control of brucellosis. Although live attenuated vaccines play important roles in the prevention of this disease, they also have several limitations, such as residual virulence and difficulty in the differentiation of immunisation and infection. We developed and evaluated a new bacteria ghost vaccine of Brucella abortus A19 by a new double inactivation method. The results showed that the bacterial ghost vaccine of Brucella represents a more safe and efficient vaccine for brucellosis. We further characterised the antigenic components and signatures of the vaccine candidate A19BG. Here, we utilised a mass spectrometry-based label-free relative quantitative proteomics approach to investigate the global proteomics changes in A19BGs compared to its parental A19. The proteomic analysis identified 2014 proteins, 1116 of which were differentially expressed compared with those in A19. The common immunological proteins of OMPs (Bcsp31, Omp25, Omp10, Omp19, Omp28, and Omp2a), HSPs (DnaK, GroS, and GroL), and SodC were enriched in the proteome of A19BG. By protein micro array-based antibody profiling, significant differences were observed between A19BG and A19 immune response, and a number of signature immunogenic proteins were identified. Two of these proteins, the BMEII0032 and BMEI0892 proteins were significantly different (P < 0.01) in distinguishing between A19 and A19BG immune sera and were identified as differential diagnostic antigens for the A19BG vaccine candidate. In conclusion, using comparative proteomics and antibody profiling, protein components and signature antigens were identified for the ghost vaccine candidate A19BG, which are valuable for further developing the vaccine and its monitoring assays.